Implementation Of Good Corporate Governance Principles On Company Performance Of PT. Vale Indonesia Tbk. Sorowako - Asha Aprilla, Asha Aprilla; Muhammad Darwis; Aslinda; Haedar Akib; Muh. Rizal S (Business Research and Administration Innovation, 2025)
This study aims to determine how much influence the Implementation of Good Corporate Governance (GCG) Principles has on the performance of PT. Vale Indonesia Tbk. Sorowako. This research uses a quantitative method with an associative descriptive research type to examine the relationship between the variables systematically. Data collection techniques used include questionnaires, documentation, and direct observation to obtain accurate and comprehensive information. The population in this study consisted of 2,964 employees, and the sampling method applied was the Slovin formula, which resulted in a sample of 97 respondents. The data obtained from the research were processed using the SPSS 25 application, which consisted of validity and reliability tests, descriptive data analysis, and inferential analysis to test the research hypotheses. Based on the results of the study, it was found that: (1) the implementation of Good Corporate Governance principles is categorized as very high, and company performance also falls into the very high category. (2) The correlation coefficient is 0.875, which indicates that the relationship between the implementation of GCG principles and company performance is very strong. Furthermore, the coefficient of determination is 0.766 or 76.6%, which means that the implementation of GCG principles contributes 76.6% to company performance, assuming other factors remain constant.